Auto mania : cars, consumers, and the environment - McCarthy, Tom, 1959- (Yale University Press, 2007)
"The twentieth-century American experience with the automobile has much to tell us about the relationship between consumer capitalism and the environment, Tom McCarthy contends. In Auto Mania he presents the first environmental history of the automobile that shows how consumer desire (and manufacturer decisions) created impacts across the product life cycle - from raw material extraction to manufacturing to consumer use to disposal."--Jacket